Rukhani Zhangyru as the cornerstone in the foreign cultural policy of Kazakhstan - Kamilla Sheryazdanova, Kulyash Tuleuova,; Alpeisov, Amirzhan (Opción, 2019)
The article aims to investigate how the implemented Rukhani Zhangyru program makes a contribution to the formation of foreign cultural policy of Kazakhstan and the creation of national branding via comparative quantitative research methods. As a result, during 2017 - 2018 grandiose work on advance and popularization of the national culture of Kazakhstan was done that was promoted by the program Rukhani Zhangyru. In conclusion, Kazakhstan’s prospects for the brand formation of the country as the Countries of the Great steppe were deep considered.